Analysis of Factors Affecting Income Inequality in Indonesia From 2016 - 2021 - Deni Anggreani Sutomo (AIBPM Publisher, 2022)
The purpose of this research is to look at the impact of human resources, minimum salaries, infrastructure, and investment on income disparity in Indonesia from 2010 to 2022. This study employs quantitative descriptive analysis with secondary data spanning the years 2010 to 2022. Data from the CSA and the Ministry of Finance are used in this analysis. Secondary data comprises economic data, particularly GDP figures, as well as scientific papers, books, and journals. Because of its quantitative nature, structural equation modeling (SEM) is applied (combining time series and cross section). This study's model has gone through construction selection and testing to become an estimating model. SEM can be used to determine the relationship between human resources, minimum wages, infrastructure, and investment, and employment, economic growth, and income. The findings indicate that all variables have a negative and significant effect on income inequality. This suggests that improving human resources, the minimum wage, infrastructure, and investment will be followed by a reduction in income inequality in Indonesia.Keywords: Human Resources, Minimum Wage, Infrastructure, Investment, Income Inequality